Socioeconomic Inequalities in Times of COVID-19 Lockdown: Prevalence and Related-Differences in Measures of Anxiety and Stress in Palestine - Al Zabadi, Hamzeh; Haj-Yahya, Maryam; Yaseen, Noor; Alhroub, Thair (Frontiers in Psychology, 2022)
Background Implementation of quarantine and lockdown to COVID-19 pandemic has created dramatic negative psychological impact mainly the general population’s health worldwide. We aimed to assess the prevalence and predictors of anxiety and stress severity among the Palestinian population. Methods A cross-sectional web-based survey was conducted. An anonymous online questionnaire and snowball recruiting technique were used to target the general public in Palestine between 6 and 16 April, 2020 during COVID-19 pandemic lockdowns. Multivariate logistic regression models were developed for the outcome variables. Results Of the 2819 individuals who completed the questionnaire, more than two thirds of them (72.6%) were females. Nearly (83.5%), were residing at the West Bank. The mean age of participants was 29.47 (SD = 10.97) years. The anxiety prevalence was (25.15%) with (20.08%) had mild/moderate severity. The stress prevalence was (38.77%) with (22.21%) had mild/moderate severity. The prevalence of both anxiety and stress was (20.3%). In multivariate analysis, exposure to confirmed case of COVID-19, inadequacy of food supply and jobs that acquire leaving home during lockdown were significantly related to higher anxiety degree. As for stress, low monthly income, cohabitation with a person of a high-risk group and inadequacy of food supply were significantly related to higher stress degree. Conclusion Young adults with low socioeconomic status and inadequate food supply were more likely to have a higher degree of stress and/or anxiety. Providing alternative economical sources for those in need, and spreading more awareness regarding the pandemic, supporting the population’s psychological wellbeing, community connection and the availability of specialist mental health services are crucial to overcome the mental impacts of COVID-19 in Palestine.